Bridelia ferruginea Benth. (Euphorbiaceae) mitigates oxidative imbalance and lipotoxicity, with concomitant modulation of insulin signaling pathways via GLUT4 upregulation in hepatic tissues of diabetic rats. (10th February 2022) - Oyebode, Olajumoke A.; Erukainure, Ochuko L.; Chuturgoon, Anil A.; Ghazi, Terisha; Naidoo, Pragalathan; Chukwuma, Chika I.; Islam, Md. Shahidul
Abstract: Ethnopharmacological relevance: Bridelia ferruginea Benth. (Euphorbiaceae) is among the medicinal plants commonly used for the management of type 2 diabetes (T2D) and its complications. Aim of the study: The hepato-therapeutic effect of the butanol fraction of Bridelia ferruginea leaves was investigated in diabetic rats. Methods: The butanol fraction of B. ferruginea was given to type 2 diabetic rats at both low and high doses (150 and 300 mg/kg bodyweight, respectively), while metformin and glibenclamide served as the standard anti-diabetic drugs. A normal toxicological group was administered a high dose of the fraction. At the end of the experimental period, the rats were sacrificed, and their livers and psoas muscle collected. The liver was assayed for oxidative stress markers, liver glycogen content, lipid metabolite profile (using GC-MS) and their metabolic pathways were analyzed using the MetaboAnalyst 5.0 online server. The expression of GLUT4 was also assayed in the liver and muscle as well as the identification of signaling pathways associated with GLUT4 expression using the Enrichr online server. In silico molecular docking was used to investigate the molecular interactions of some postulated compound found in B. ferruginea with GLUT4. The ability of the fraction to stimulate muscle glucose uptake was determined in isolated rat psoas muscle ex vivo . Results: Treatment with the high dose of fraction caused an inhibition of lipid peroxidation as well as the elevation of catalase, SOD, glutathione reductase and glutathione peroxidase activities in the rat liver. There was an increased expression of GLUT4 in livers and muscles of diabetic rats following treatment with B. ferruginea . Treatment with the fraction also caused inactivation of diabetes-activated pathways and changes in the distribution of the hepatic lipid metabolites. Molecular docking analysis revealed strong molecular interactions of pyrogallol and sitosterol with GLUT4. Conclusions: These data illustrate the hepato-protective effect of B. ferruginea in diabetic rats which compare favorably with the tested anti-diabetic drugs (metformin and glibenclamide). Graphical abstract: Image 1